Implementasi Paralel Bubble Sort dengan Menggunakan MPICH2 dan Perbandingannya dengan Implementasi Sekuensial - Rosani, Erna; Imaculata Inriani, Maria; Asmara, Jimi (Institut Informatika Dan Bisnis Darmajaya, 2025)
This research is motivated by the need for efficient sorting algorithms for large amounts of data. The objective of this research is to implement the Bubble Sort algorithm in parallel using MPICH2 and compare its performance with sequential implementations. The research method involved testing parallel and sequential Bubble Sort programs on datasets of varying sizes (10, 100, 1,000, 10,000, and 100,000 elements). The experimental results show that parallel Bubble Sort performs better than sequential Bubble Sort, especially for large amounts of data. The speed-up achieved was 4.44 times faster on a dataset of 100,000 elements. However, for small data sets, sequential Bubble Sort is more efficient due to the communication overhead between processes in parallel Bubble Sort.